The effects of a maternal advanced glycation end product-rich diet on somatic features, reflex ontogeny and metabolic parameters of offspring mice. Issue 6 (7th June 2018) - Csongová, Melinda; Gurecká, Radana; Koborová, Ivana; Celec, Peter; Domonkos, Emese; Uličná, Oľga; Somoza, Veronika; Šebeková, Katarína
Abstract : A maternal AGE-rich diet during pregnancy affects the early neuromotor development of offspring consuming a standard diet, and the metabolic status of male progeny. Abstract : Maternal exposure to a Western type diet during pregnancy might predispose the offspring to manifestation of metabolic and behavioral disturbances in later life. The Western type diet contains large amounts of advanced glycation end products (AGEs). In humans and experimental rodents, the intake of an AGE-rich diet (AGE-RD) negatively affected glucose homeostasis, and initiated the production of reactive oxygen species. Rats consuming the AGE-RD presented changes in behavior. It remains unclear whether maternal intake of the AGE-RD might affect developmental plasticity in offspring. We examined early somatic (weight, incisor eruption, ear unfolding, and eye opening) and neuromotor development, oxidative status, insulin sensitivity (HOMA index) and locomotor activity assessed in PhenoTyper cages in the offspring of mice fed during pregnancy with either the AGE-RD (25% bread crusts/75% control chow) or control chow. Until weaning, the somatic development of offspring did not differ between the two dietary groups. The AGE-RD offspring manifested physiological reflexes (auditory startle, eye lid, ear twitch and righting reflexes) earlier. As young adults, the male offspring of the AGE-RD dams were heavier and less insulin sensitive compared with their control counterparts. The AGE-RD offspring showed higher locomotor activity during the active phase. Our data indicate that the maternal AGE-RD during pregnancy might accelerate the maturation of reflexes in offspring, predispose the male progeny to weight gain and affect their glucose homeostasis. These effects manifest without the direct consumption of the AGE-RD by offspring. Further work is needed to determine the mechanisms by which the maternal AGE-RD affects neurobehavioral pathways in offspring, as well as sex differences in adverse metabolic responses.